Pengaruh Kehadiran Apoteker Terhadap Pengelolaan Obat Pada Apotek di Provinsi Banten - Hartuti, Wiwi; Sasongko, Rhatih Eka (Eruditio : Indonesia Journal of Food and Drug Safety, 2023)
Drug management under applicable guidelines greatly supports the   establishment of quality pharmaceutical care to assure the availability of safe, qualified, useful and affordable pharmaceutical products, medical devices, and medical consumables. Generally, the pharmacy cares is are related to presence of pharmacist which is not based on applicable guidelines. In facts, there is an indication  that the presence of pharmacists in pharmacy cares  have been  low. Previous studies showed the percentage of pharmacist attendance at the pharmacy cares was inadequate and it had an affect on pharmaceutical services. There are three aims of this  study namely: (1) to obtain data of the pharmacist’s presence at pharmacy cares in Banten Province, (2) to investigate the correlation  of the pharmacist's presence and drug management at the pharmacy cares, and (3) to gain information about the implementation of drug management in pharmacy cares based on BPOM Regulation No. 24 of 2021. The study was conducted using sample data of surveillance inspection of pharmacy cares in several  districts/cities located in Banten Province from February 2020 to December 2021. Data analysis was processed  using the Spearman correlation test quantitative analysis method with SPSS type 26. This study showed that the presence of pharmacists at pharmacy facilities in Banten Province was 36.25% (58 of 160 pharmacists). Spearman correlation test concludes there was a positive correlation between pharmacist presence and drug management at the pharmacy cares. Drug management in pharmacy cares under BPOM Regulation Number 24 of 2021 was insufficient in drug procurement, transfer, and storage aspects. The three highest findings in the critical category were drug procurement (14,38%), drug transfer (9,38%), and drug storage (3,13%). The three highest findings in the major category were drug storage (61,88%, drug procurement (50,63 %), and drug recording report (46,25%). Drug management in pharmacies was pharmacists' responsibility, but inadequate pharmacists' presence had an impact on discrepancy of  drug management between the guidelines.